2010
DOI: 10.1016/s1001-0742(09)60145-5
|View full text |Cite
|
Sign up to set email alerts
|

In situ DRIFTS study of hygroscopic behavior of mineral aerosol

Abstract: In situ diffusion reflectance infrared Fourier transform spectroscopy was used to study the water adsorption on mineral oxides (SiO 2 , α-Al 2 O 3 , MgO, Fe 2 O 3 , TiO 2 ). The results showed that all the water adsorption isotherms were well fitted with the Brunauer-EmmettTeller (BET)-III type equation, with the calculated monolayers occurring at 24%-30% relative humidity. It showed that about 1-5 layers of water adsorbed on oxides surfaces in ambient relative humidity (20%-90%). The measured deliquescence re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
108
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(118 citation statements)
references
References 21 publications
(25 reference statements)
9
108
1
Order By: Relevance
“…It may be noted that the γ values measured in the present study for RH between 20 and 80 % are close to that measured for the uptake coefficient of HO 2 on water, γ ≥ 0.01 (Hanson et al, 1992). This fact seems to correlate, at least qualitatively, with the available data for the adsorption of water on mineral oxides (Goodman et al, 2001;Ma et al, 2010). Indeed, it was reported that water adsorption to SiO 2 , Al 2 O 3 , MgO, Fe 2 O 3 , and TiO 2 (which are components of ATD) could be well described with the Brunauer-Emmett-Teller (BET) type isotherm, with the monolayer coverage occurring between 20 and 30 % relative humidity (Goodman et al, 2001;Ma et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It may be noted that the γ values measured in the present study for RH between 20 and 80 % are close to that measured for the uptake coefficient of HO 2 on water, γ ≥ 0.01 (Hanson et al, 1992). This fact seems to correlate, at least qualitatively, with the available data for the adsorption of water on mineral oxides (Goodman et al, 2001;Ma et al, 2010). Indeed, it was reported that water adsorption to SiO 2 , Al 2 O 3 , MgO, Fe 2 O 3 , and TiO 2 (which are components of ATD) could be well described with the Brunauer-Emmett-Teller (BET) type isotherm, with the monolayer coverage occurring between 20 and 30 % relative humidity (Goodman et al, 2001;Ma et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…This fact seems to correlate, at least qualitatively, with the available data for the adsorption of water on mineral oxides (Goodman et al, 2001;Ma et al, 2010). Indeed, it was reported that water adsorption to SiO 2 , Al 2 O 3 , MgO, Fe 2 O 3 , and TiO 2 (which are components of ATD) could be well described with the Brunauer-Emmett-Teller (BET) type isotherm, with the monolayer coverage occurring between 20 and 30 % relative humidity (Goodman et al, 2001;Ma et al, 2010). In only one previous product study of HO 2 interaction with solid surface (Loukhovitskaya et al, 2009) H 2 O 2 was identified as the main gaseous product of the HO 2 reaction with the surface of NaBr.…”
Section: Discussionsupporting
confidence: 67%
“…The RH dependence of γ observed in the present study (decrease of the uptake coefficient upon increase of RH) points to the role of water rather as blocking the available active sites on the surface and seems to be in line, at least qualitatively, with the available data for the adsorption of water on mineral oxides. 29,30 Indeed, it was reported that water adsorption to SiO 2 , Al 2 O 3 , MgO, Fe 2 O 3 , and TiO 2 (which are components of ATD) could be well described with the Brunauer−Emmett−Teller (BET) type isotherm, with the monolayer coverage occurring between 20 and 30% relative humidity. 29,30 It can be noted that, in previous studies, similar negative dependence on RH was observed also for the uptake coefficient of H 2 O 2 on SiO 2 , Al 2 O 3 , 31 and TiO 2 .…”
Section: Reactionmentioning
confidence: 99%
“…For example, adsorbed water can be measured by Fourier-transform infrared spectroscopy by its infrared absorption at around 3400 and 1645 cm −1 (Goodman et al, 2001;Frinak et al, 2005;Ma et al, 2010a). However, it is nontrivial to convert infrared absorption intensity to the amount of adsorbed water (Schuttlefield et al, 2007a;Tang et al, 2016).…”
mentioning
confidence: 99%